Periphytic algae dynamics in lentic ecosystems in the Brazilian semiarid - Cordeiro,R. S. (2017)
Abstract The hydrological periods drive the structure and organization of aquatic communities in semiarid regions. We hypothesize that a decrease of the precipitation during the dry period will favor the development of the periphytic algal community, leading to higher richness and density in this period. To test this hypothesis, we investigated the changes in the periphytic algal community structure in three shallow and eutrophic ecosystems of the Brazilian semiarid. The sampling was performed between 2007 and 2010 at two-mensal intervals. The sampling of periphytic algal was performed in aquatic macrophytes and rocks. The abiotic variables were analyzed simultaneously. Dominance in diatoms, cyanobacteria and chlorophytes, respectively, was observed in two periods. In the dry period, waters were alkaline and had high concentrations of nitrate and total phosphorus associated with the highest densities of Bacillariophyceae. In the rainy period the water was warmer, oxygenated and high concentrations of ammonia and soluble reactive phosphorus with diatoms remained dominant but with reduced density, while cyanobacteria and chlorophytes increased. Overall, periphytic algal community composition no responded to changes in the hydrological periods. However, the hydrological periods altered the dynamics of periphytic algal community, supported by the alternation of the most representative classes (diatoms and cyanobacteria) between the hydrologic periods. Our data suggest that the morphometric and chemical and physical characteristics of lentic aquatic ecosystems studied were more important in the dynamics of periphytic algal community than the hydrological periods and types of substrates.